MODERN APPROACH TO TREATMENT OF COMMUNITY-ACQUIRED PNEUMONIA, COMPLICATED EXUDATIVE PLEURITIS - Vakhnenko, A.V.; Moiseeva, N.V. (World of Medicine and Biology, 2014)
One of the most common diseases of mankind remain respiratory diseases, which are associated with an increase of viral infection, but this increased volume of patients on complicated CP of exudative pleuritis. On the other hand CP often occurs on the background of hypertension, which is manifested by stagnation. There is enough information about the etiopathogenesis and treatment of CP, but the question of the differential selection of treatment of complicated community-acquired pneumonia in patients with different concomitant diseases, drugs affecting different pathogenetic links diseases are not given adequate attention. The aim of this study is to optimize the treatment of patients with CP, exudative pleuritis complicated by the presence of AH. Studies have demonstrated that the use of combined treatment of patients on CP with exudative pleuritis complicated by IHD, hypertension drug combination Tivortin aspartate and britomar led to more significant changes in the values of saturation, blood biochemical parameters, as well as accelerated the recovery of patients, which was confirmed by the positive dynamics for radiological studies greatly improved for all parameters of quality of life, which was reflected in a significant decrease in functional limitations and high social activity in patients. And despite the higher cost of these drugs compared with traditional treatment, overall treatment costs for patient decreased significantly.